Emotion Socialization in the Context of Childhood Cancer: Perceptions of Parental Support Promotes Posttraumatic Growth. (2nd August 2016) - Howard Sharp, Katianne M.; Willard, Victoria W.; Barnes, Sarah; Tillery, Rachel; Long, Alanna; Phipps, Sean
Abstract : Objective Examined youth's perceptions of parental reactions to youth's cancer and non-cancer event-related distress and the link between perceptions of parental reactions and youth posttraumatic growth (PTG). Method Participants included 201 youth (8–21 years) with a history of cancer. Participants self-identified their most stressful life event, which were characterized as cancer or non-cancer related, and then completed measures in reference to this event assessing (1) their perceptions of parent reactions to event-related distress and (2) PTG. Results Youth who identified a cancer-related event perceived their parents as reacting with more support and reassurance/distraction than those who identified a non-cancer event. Perceptions of parental support, reassurance/distraction, and magnification of youth distress were associated with more PTG, with event type (cancer vs. non-cancer) indirectly predicting PTG through perceptions of parental support. Conclusion Youth perceive their parents as reacting differently to cancer versus non-cancer distress, which is in turn predictive of their perceptions of growth. Findings suggest that parental support and reassurance/distraction are possible mechanisms facilitating resilience and growth in children with cancer.